Design and implementation of 3 Axis Magnetic Field Meter - Chin Paik Leang (Universiti Malaysia Perlis, 2008)
Magnetic field meter, (sometimes referred to as an magnetic field detector) is a scientific instrument for measuring magnetic field radiation. This project is to construct the three axis portable magnetic field meter. The purpose of this project is use to detect the magnetic field at 3 axis (X, Y, Z) that are generate by such things as power lines, electric appliances, radio waves, and microwaves .The magnetic field meter also have other function like display the maximum value for magnetic field. Magnetic field meters usually measure radiation in milliGauss unit. Generally, this project consists 4 part there are sensor, amplifying and digitizing (amplifier & multiplexer & analog to digital converter), microcontroller and liquid crystal display (LCD). Sensor as a function to detect the magnetic field on electrical appliance then will send the signal to amplifier. This project is to detect 3 axis magnetic field (X, Y, Z), so three amplifier are used. Output from each amplifier will send to input of four channel multiplexer. The selector (A, B) of four channel multiplexer is control by micro-controller so that one input can be selected once at the time. Output from multiplexer is DC so ADC is needed as a function to convert the analog signal to digital signal. The ADC input is taken from output of multiplexer. For microcontroller part, it will fetch the signal from output of ADC and display at LCD. Finally, the value of magnetic field will display on LCD in milliGauss unit.